PICTURING “CORONAVIRUS” IN NEWS ON THE WEB (NOW) CORPUS: A CORPUS LINGUISTIC STUDY - Eva Tuckyta Sari Sujatna; Meita Lukitawati Sujatna; Larasati Puspa Martani Sugianto; Putri Muthia Saraswati Muljono (Universitas Padjadjaran, 2022)
Recently, “coronavirus” is viral since the outbreak firstly reported in Wuhan and today become a pandemic. The writers found the word “coronavirus” in News on the Web (NOW) corpus in a huge number. This research applied mixed-method in which quantitative and qualitative approaches are combined to provide a more complete understanding of the research. The objectives of the research are firstly, to portray the distribution and the time line of the word “coronavirus” in NOW corpus, and to identify the pair of the word “coronavirus” in NOW corpus. Based on the analysis of the data, firstly, it was reported on April 27, 2020 many countries, including Australia, New Zealand, Iran, and Spain did coronavirus lockdown to slower the growing number of coronavirus infected people and the number of the word “coronavirus” in NOW corpus increased significantly from 16,073 to 64,100 times. Secondly, it was found that the compound words containing the word “coronavirus” related to health terminologies: the compound words containing two words as nouns, the compound words containing three words as nouns, the compound words containing three words as an adjective and two nouns, compound words containing four words as nouns, and the compound words containing four words as an adjective and three nouns.